Controlling windscreen wiper vibration through yaw angle adjustments: a study of dynamic contact behavior using fluorescence observation - Tadokoro, Chiharu; Kobayashi, Hiroaki; Sueda, Miwa; Nagamine, Takuo; Vlădescu, Sorin-Cristian; Reddyhoff, Tom; Nakano, Ken (Frontiers in Mechanical Engineering, 2024)
Friction-induced vibration in the wiper system of passenger cars not only causes impaired visibility as a result of uneven water film distribution on the windscreen surface, but also leads to noise problems by transmitting vibrations as sound to the passengers. In this study, a novel experimental apparatus was developed to simulate the wiper system, enabling the change in normal support stiffness and the precise adjustment of the yaw angles of a shortened rubber blade and its flexible base relative to the drive direction of a glass plate. The use of fluorescence observation provided a significant advantage, enabling precise measurements of the position of the rubber blade tip and the water film thickness in the contact area of the rubber blade and the glass plate during operation. In conjunction with this, an accelerometer and a gap sensor were employed to measure the normal and tangential motions of the support structures, respectively. This comprehensive setup allows for precise control of blade support conditions, and provides accurate measurement for motions of rubber blade and support structures, making it a powerful tool for investigating friction-induced vibration in the wiper system. The experimental results clearly demonstrated the effectiveness of applying large yaw angles to both the rubber blade and the flexible base in suppressing friction-induced vibration, resulting in smooth motion at any drive speed. These findings have the potential to improve wiper performances under actual operating conditions.